2017
DOI: 10.1007/s10905-017-9647-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk Proneness or Social Withdrawal? The Effects of Shortened Life Expectancy on the Expression of Rescue Behavior in Workers of the ant Formica cinerea (Hymenoptera: Formicidae)

Abstract: In social insects behavioral consequences of shortened life expectancy include, among others, increased risk proneness and social withdrawal. We investigated the impact of experimental shortening of life expectancy of foragers of the ant Formica cinerea achieved by their exposure to carbon dioxide on the expression of rescue behavior, risky pro-social behavior, tested by means of two bioassays during which a single worker (rescuer) was confronted with a nestmate (victim) attacked by a predator (antlion larva c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 59 publications
4
21
0
Order By: Relevance
“…This demonstrated that, at least in some ant species, the detection of rescue behavior might depend on the test type used for detection. Taken together with the results of another study demonstrating differences between test types [ 43 ], these findings showed that the context of rescue action, in terms of the source of endangerment to the victims, matters to potential rescuers.…”
Section: Overview Of Work On Rescue Behavior In Antssupporting
confidence: 71%
See 2 more Smart Citations
“…This demonstrated that, at least in some ant species, the detection of rescue behavior might depend on the test type used for detection. Taken together with the results of another study demonstrating differences between test types [ 43 ], these findings showed that the context of rescue action, in terms of the source of endangerment to the victims, matters to potential rescuers.…”
Section: Overview Of Work On Rescue Behavior In Antssupporting
confidence: 71%
“…Using laboratory tests with F. cinerea victims caught by predatory antlions and ensnared by nylon threads, Miler et al [ 43 ] tested whether potential rescuers with differing life expectancies display different levels of rescue behavior. In the previous study on life expectancy, but from the perspective of the victims [ 38 ], the two reasons for the effect of life expectancy gave similar predictions; here, the predictions diverged.…”
Section: Overview Of Work On Rescue Behavior In Antsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it might have been expected that ants with shortened life expectancy will show higher propensity to engage in risky rescue behavior, However, many studies reported, that in ants shortened worker life expectancy may also lead to social withdrawal (Hölldobler and Wilson 1990;korczyńska 2001;uGelviG and creMer 2007;Heinze and Wal-Ter 2010;Bos et al 2011;diez et al 2015; leclerc and deTrain 2017). The findings of Miler (2016) and Miler et al (2017b) can thus be interpreted, too, in terms of the induction of social withdrawal. If so, these findings suggest that experimental studies of ant rescue behavior may prove to be of importance for comparative research devoted to causal factors underlying social withdraw-should also be generally suited to the circumstances, and should not be inherently rewarding or beneficial to the rescuer (noWbaHari and Hollis 2010; Hollis and noWbaHari 2013a).…”
Section: Dyadic Nestmate Rescue Tests In the Research On Ant Pro-socimentioning
confidence: 91%
“…A series of experiments of Miler and his coworkers explored various factors influencing nestmate rescue behavior of workers of F. cinerea during bioassays with antlion larvae (Miler 2016) and artificial snares (Miler and kuszeWska 2017), and during both these types of bioassays (Miler et al 2017a(Miler et al , 2017b. These studies revealed, among others, that workers of F. cinerea with life expectancy experimentally shortened by exposure to carbon dioxide less efficiently triggered rescue behavior of their nestmates during the bioassays with antlion larvae (Miler 2016), and less readily engaged in rescue behavior in response to a nestmate entrapped in an artificial snare (Miler et al 2017b). These findings were surprising, as in ants shortened life expectancy often leads to increased readiness to engage in risky tasks (Moroń et al 2008(Moroń et al , 2012.…”
Section: Dyadic Nestmate Rescue Tests In the Research On Ant Pro-socimentioning
confidence: 99%